Mastering Tailwind CSS 3.0 : build two dynamic projects. (Packt Publishing, 2023)
This course embarks on a journey to become a master of this powerful CSS framework. Tailwind CSS has gained immense popularity among developers for its utility-first approach and simplicity. In this course, you will not only learn the ins and outs of Tailwind CSS but also apply your knowledge to build two remarkable projects: Instagram and Tesla clones. Starting with the fundamentals, you will familiarize yourself with the latest version of Tailwind CSS 3.0 and understand its core concepts. Discover how to leverage utility classes to create responsive websites, effectively use Flexbox and Grid for layout design, and implement powerful features such as typography, transitions, and animations. The course takes a hands-on approach, providing you with real-world projects to work on. You will dive into building the Tesla clone, recreating its header, main sections, and footer. Throughout the projects, you will learn valuable techniques and best practices, enabling you to create pixel-perfect designs with ease. Next, you will tackle the Instagram clone, replicating its header, stories section, post section, and mini profile. By the end of this course, you will have a strong foundation in Tailwind CSS and the confidence to build beautiful and responsive websites. It will also provide you with the skills to create professional web interfaces using Tailwind CSS. What You Will Learn Learn the best practices of Tailwind CSS 3.0 Create responsive websites using utility classes, Flexbox, and Grid Build an Instagram clone with header, stories section, and post section Develop a Tesla clone with header, main sections, and footer Utilize Tailwind CSS official plugins such as scrollbar and form Implement advanced features such as transitions, animations, and custom styles Audience This course is designed for web developers of all levels who want to expand their skills in modern CSS development. Whether you are a beginner looking to learn Tailwind CSS from scratch or an experienced developer seeking to enhance your web design toolkit, you will gain essential skills from this course. By building Instagram and Tesla clones, you will gain practical skills applicable to a wide range of web development projects. This course is also suitable for designers looking to improve their CSS workflow and create stunning, responsive websites without sacrificing flexibility. You would just need a basic familiarity with CSS. About The Author Dr. Sahand Ghavidel: Dr. Sahand Ghavidel holds degrees in mathematics, electrical, and computer science, and has earned a doctoral degree from the Faculty of Engineering and IT, University of Technology Sydney. He has researched for more than a decade about artificial algorithms and optimization. He has won several awards for his outstanding research and has published more than 40 ISI journals and attended many international conferences. The number of people using and citing Sahand's publications is significantly high, which is more than 1,600 citations, according to Google Scholar (April, 2021). He was also awarded the outstanding reviewer in the "International Journal of Electrical Power & Energy Systems" with a CiteScore of 5.79 in recognition of his contributions added to the quality of the journal. Sahand, with 15+ years of programming experience, started coding at 12 with Visual Basic. He has since built countless websites and apps using JavaScript, Python, and more.